Abatacept treatment reduces disease activity in early primary Sjögren's syndrome (open-label proof of concept ASAP study). Issue 7 (28th January 2014) - Meiners, P M; Vissink, A; Kroese, F G M; Spijkervet, F K L; Smitt-Kamminga, N Sillevis; Abdulahad, W H; Bulthuis-Kuiper, J; Brouwer, E; Arends, S; Bootsma, H
Abstract : Objective: To assess the efficacy and safety of abatacept in patients with early and active primary Sjögren's syndrome (pSS). Methods: All 15 patients (12 women, three men) included in the open-label Active Sjögren Abatacept Pilot study met the revised American-European Consensus Group criteria for pSS and were biological disease-modifying antirheumatic drug-naive. Patients were treated with eight intravenous abatacept infusions on days 1, 15 and 29 and every 4 weeks thereafter. Follow-up was conducted at 4, 12, 24 (on treatment), 36 and 48 weeks (off treatment). Disease activity was assessed with European League Against Rheumatism (EULAR) Sjögren's Syndrome Disease Activity Index (ESSDAI) and EULAR Sjögren's Syndrome Patient Reported Index (ESSPRI). Several other functional, laboratory and subjective variables were analysed. Generalised estimating equations were used to analyse parameters over time. Results: ESSDAI, ESSPRI, rheumatoid factor and IgG levels decreased significantly during abatacept treatment and increased post-treatment. Salivary and lacrimal gland function did not change during treatment. Fatigue and health-related quality of life (HR-QoL) improved significantly during treatment. No serious side effects or infections were seen. Conclusions: In this open-label study, abatacept treatment is effective, safe and well tolerated, and results in improved disease activity, laboratory parameters, fatigue and HR-QoL in patients with early and active pSS. Trial registration number: 2009-015558-40.